A dictionary of early Christian biography and literature to the end of the sixth century A.D., with an account of the principal sects and heresies - Wace, Henry; Piercy, William C. (USA Hendrickson, 1999)
A reference guide to over 800 Christian men and women, heretics and sects of the first six centuries
Includes bibliographical references.
reprinted from the edition originally titled " A dictionary of Christian biography and literature", published London, John Murray, 1911
Keywords: Church history -- primitive and early church -- biography -- dictionaries; Church history -- primitive and early church -- literature -- dictionaries; Church history -- primitive and early church -- heresies -- dictionaries; Church history -- primitive and early church -- sects -- dictionaries